The practice of banking : a student centered text - Olalusi, Foluso (Akure : Trudon Publishers, 1989)
The book has been written with the Nigerian audience in mind, hence, examples and cases where possible, have been drawn from the local environment, although some foreign cases have got to be cited in the absence of local equivalents to illustrate basic principles. The various services offered by the banks is focus in chapters 1-5, while chapters 6-8 centers on the principles and practice of bank lending. Forms of securities for bank advances is considered in chapters 9-14. The relationship between a banker and the customer is exhaustively discussed in chapter 15, while chapters 16 and 17 dealt with negotiable instruments with particular emphasis on cheques. The peculiar problems of bankrupt customers, security problems in banks and the interrelationship between banks and governments have closely examined in chapters 18-20.
Volume 1.
Includes bibliographic references and index.
rpm 03/05/2018
Loans
Keywords: Banking; Banking practice